Penggunaan Three-Tier Diagnostic Test Untuk Pemetaan Tingkat Penguasaan Elektrokimia Mahasiswa Kimia Semester II - Elvian Anggelina Soru; Hardin Foster Rares; Joice Caroles (Oxygenius Journal Of Chemistry Education, 2020)
The purpose of this study was to determine the level of understanding of concept maps of semester II chemistry students using a three-tier diagnostic test on electrochemical subjects with multimedia-based learning. The research was carried out in the Department of Chemistry, FMIPA, UNIMA in the even semester of the 2018/2019 school year. The research method used is One-shot Case, with a sample of the research that is a class of chemistry classes for a certain year as many as 12 people. Multimedia instruments are made by utilizing animation and video from the internet which is packaged in Ms. Power point, and the electrochemical three-tier diagnostic test instrument is made according to the subject being taught. Then the test instrument was validated and 15 questions were produced. It was found the map data on the level of understanding of electrochemical concepts namely the average number of students who understood the concept by 41.6%, the average number of students experiencing misconceptions both misconceptions (+), misconceptions (-) and misconceptions by 30.033%, average number students do not understand the concept as much as 11.1%, there are 8.3% students who are not sure of the concept they have, and 8.3% there are students who do not understand the concept of electrochemistry. Thus, it was concluded that a three-tier electrochemical diagnostic test was able to reveal a map of students' level of understanding of the chosen topic